Implementation of leadership training policy in the local government of Gorontalo regency - Rachman, Azis; Sudarsono, Sudarsono; Darise, Annisa Giana (International research journal of management, IT and social sciences, 2023)
The aims of this study were: (1) to find out the implementation of the Leadership Training Policy within the Local Government of Gorontalao Regency in terms of training planning, training implementation, and training evaluation. (2) to find out the factors that determine the implementation of the Leadership Training Policy within the Regional Government of Gorontalo Regency. This study used a qualitative approach and descriptive research using data collection techniques through observation, in-depth interviews, and documentation. Data analysis techniques were carried out through the stages of data reduction, data presentation, and conclusion. The results of the study show that (1) the Implementation of the Leadership Training Policy in the Regional Government of Gorontalo Regency seen from the training planning has been carried out maximally, while when viewed from the training implementation and training evaluation it has not been carried out optimally. (2) Communication, Resources, Executor’s Attitude, and Bureaucratic Structure are the factors that determine the Implementation of Leadership Training Policy in the Gorontalo Regency Government, where Communication, Implementer’s Attitude, and Bureaucratic Structure have been well implemented. Meanwhile, the main problem with the non-implementation of Leadership Training is the unavailability of a budget from the regional government.